Absorption and photoluminescent spectra of dimethylaniline ethylene ketone dyes in isotropic solvents - Gorishnyi, M.P.; Shevchuk, A.F.; Manzhara, V.S.; Koval'chuk, A.V.; Koval'chuk, T.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Absorption and photoluminescent spectra of dimethylaniline ethylene ketone dyes of two types K1 and K2 in a series of isotropic solvents were studied. It was shown that the photoluminescent spectra depend both on nature of solvent (formation of associates with solvent owing to hydrogen bonds between the dye and alcohol or aggregates of dye molecules) and the dye concentration (concentration decay). The frequencies of electron transitions and frequency of intramolecular fluctuation were determined, and conclusions concerning the nature of absorption bands were made.